Maternal taurine as a modulator of Cl– homeostasis as well as of glycine/GABAA receptors for neocortical development - Furukawa, Tomonori; Fukuda, Atsuo (Frontiers in Cellular Neuroscience, 2023)
During brain and spinal cord development, GABA and glycine, the inhibitory neurotransmitters, cause depolarization instead of hyperpolarization in adults. Since glycine and GABAA receptors (GABAARs) are chloride (Cl -) ion channel receptor, the conversion of GABA/glycine actions during development is influenced by changes in the transmembrane Cl - gradient, which is regulated by Cl -transporters, NKCC1 (absorption) and KCC2 (expulsion).In immature neurons, inhibitory neurotransmitters are released in a non-vesicular/non-synaptic manner, transitioning to vesicular/synaptic release as the neuron matures. In other word, in immature neurons, neurotransmitters generally act tonically. Thus, the glycine/GABA system is a developmentally multimodal system that is required for neurogenesis, differentiation, migration, and synaptogenesis.The endogenous agonists for these receptors are not fully understood, we address taurine. In this review, we will discuss about the properties and function of taurine during development of neocortex. Taurine cannot be synthesized by fetuses or neonates, and is transferred from maternal blood through the placenta or maternal milk ingestion. In developing neocortex, taurine level is higher than GABA level, and taurine tonically activates GABAARs to control radial migration as a stop signal. In the marginal zone (MZ) of the developing neocortex, endogenous taurine modulates the spread of excitatory synaptic transmission, activating glycine receptors (GlyRs) as an endogenous agonist. Thus, taurine affects information processing and crucial developmental processes such as axonal growth, cell migration, and lamination in the developing cerebral cortex.Additionally, we also refer to the possible mechanism of taurine-regulating Cl -homeostasis.External taurine is uptake by taurine transporter (TauT) and regulates NKCC1 and KCC2 mediated by intracellular signaling pathway, with-no-lysine kinase 1 (WNK1) and its subsequent kinases STE20/SPS1-related proline-alanine-rich protein kinase (SPAK) and oxidative stress response kinase-1 (OSR1). Through the regulation of NKCC1 and KCC2, mediated by the WNK-SPAK/OSR1 signaling pathway, taurine plays a role in maintaining Cl - homeostasis during normal brain development.